Interactive Crossword Learning Media Based on Problem Based Learning Magnet Material in IPAS Class V Elementary School - Putu Sashi Suryani Artawan Putri; Didith Pramunditya Ambara (Journal of Education Technology, 2025)
The lack of engaging and interactive learning media has been identified as a challenge in teaching magnetic materials in the IPAS subject for fifth-grade students. Conventional methods often fail to capture students' interest and enhance their understanding. This study aims to develop and evaluate an interactive crossword learning media based on Problem-Based Learning (PBL) to address this issue. This research employs the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study involved fifth-grade students from SD No. 2 Sedang, as well as expert validators in media, instructional design, and subject content. The developed learning media underwent expert validation, individual trials, small group trials, and a field trial to assess its feasibility and effectiveness. Data were collected through validation questionnaires, observations, and pre-test and post-test instruments, analyzed using quantitative and qualitative approaches. The results indicate that the developed media is highly feasible and significantly improves student learning outcomes. The interactive and problem-solving elements enhance engagement, motivation, and comprehension. Students showed a higher level of participation and interest, making the learning process more effective and enjoyable. This study highlights the importance of integrating interactive media into learning to foster critical thinking and student engagement. The findings suggest that this approach can be applied to other subjects to improve instructional quality. Further research is recommended to refine and expand the application of interactive learning media in different educational contexts.